This is a love story ebook A novel. - Soffer, Jessica (2025)
AN INSTANT NEW YORK TIMES BESTSELLER | READ WITH JENNA BOOK CLUB PICK AS FEATURED ON TODAY “This may be the most epic love story I’ve ever, ever read.”—Jenna Bush Hager on TODAY An intimate and lyrical celebration of great love, great art, and the sacrifices we make for both For fifty years, Abe and Jane have been coming to Central Park, as starry-eyed young lovers, as frustrated and exhausted parents, as artists watching their careers take flight. They came alone when they needed to get away from each other, and together when they had something important to discuss. The Park has been their witness for half a century of love. Until now. Jane is dying, and Abe is recounting their life together as a way of keeping them going: the parts they knew—their courtship and early marriage, their blossoming creative lives—and the parts they didn’t always want to know—the determined young student of Abe’s looking for a love story of her own, and their son, Max, who believes his mother chose art over parenthood, and who has avoided love and intimacy at all costs. Told in various points of view, even in conversation with Central Park, these voices weave in and out to paint a portrait as complicated and essential as love itself. An homage to New York City, to romance, and even to loss, This Is a Love Story tenderly and suspensefully captures deep truths about life and marriage in radiant prose. It is about love that endures despite what life throws at us, or perhaps even because of it.